Comparative Analysis on Symbolic Representation of Discriminatory Expressions in Students of Multimedia Communication Engineering - Hernández Arroyo, Enrique Noé (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To identify whether the discriminatory expressions associated with racism, classism, ethnocentrism, sexism, and homophobia are duly recognized within the symbolic representations of students of different degrees of study of Multimedia Communication Engineering. The assumption resides in evaluating whether the level of study is directly linked to the discernment of discriminating phrases.MATERIAL AND METHOD: The method is based on the quantitative analysis of correlational cut; for its part, the measurement instrument is operationally structured from conventional expressions in accordance with the five types of discrimination previously stated. For data interpretation, Pearson's correlation coefficient was applied, with a significance level of 0.05.RESULTS: There is a direct and positive relationship between the degree of study and the discernment of racist and homophobic expressions. On the other hand, classist and sexist expressions present a moderate relationship. Finally, in the case of ethnocentric expressions, a scattered correlation prevails; that is, the degrees of study do not have a positive or negative correlation with respect to the discernment of phrases.CONCLUSION: It is expected to instruct about these forms of discrimination in higher level students, with the purpose of disseminating an inclusive language free of violence.
Keywords: Classism; Multimedia-Communication; Discrimination; Equality; Racism.